Preparation method of graphene / aluminum composite material for regulating and controlling Mg element interface segregation through double reinforced phases
By using a dual-reinforcement phase to regulate Mg interfacial segregation, and combining micron-sized and nano-sized silicon carbide with graphene, the problem of Mg segregation in the aluminum matrix was solved, improving the mechanical properties and interfacial bonding strength of the graphene/aluminum composite material, and achieving efficient composite material preparation.
Patent Information
- Application Number
- CN202510975454.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-10-28
AI Technical Summary
When preparing graphene or silicon carbide-aluminum alloy composites, Mg in the aluminum matrix tends to segregate near the reinforcement, disrupting the Mg-Si atomic ratio and leading to a decrease in the mechanical properties of the composite.
The method of dual-reinforcement phase regulation of Mg element interface segregation is adopted. Through mechanical ball milling and hot extrusion processes, micron silicon carbide and nano silicon carbide are combined with graphene to form a tight interface, control the diffusion direction of Mg element, reduce interface segregation, and improve interface bonding strength.
It improves the overall mechanical properties of composite materials, with an elastic modulus exceeding 90 GPa, tensile strength exceeding 630 MPa, and elongation exceeding 11.6%, while reducing environmental pollution and production costs.
Smart Images

Figure CN120843898A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing graphene / aluminum composite materials. Background Art
[0002] Graphene, as a two-dimensional nanomaterial reinforcement, has attracted widespread attention from the research community since its successful isolation. It possesses extraordinary theoretical mechanical properties: a theoretical tensile strength of approximately 130 GPa and a hardness of an astonishing 0.5-1 TPa, far exceeding that of diamond. These groundbreaking performance indicators demonstrate its extremely broad application potential in the field of composite materials. For this reason, graphene has been rapidly explored and applied to various advanced composite material systems since its inception.
[0003] Silicon carbide (SiC), as a mature ceramic reinforcement material, has long held an important position in the field of composite materials. It possesses outstanding physical properties: a hardness exceeding 9.2 on the Mohs scale (close to diamond), an elastic modulus exceeding 400 GPa, and excellent high-temperature stability, wear resistance, and chemical inertness. These outstanding performance advantages make it widely applicable in metal-based (especially aluminum-based), ceramic-based, and polymer-based composite materials. For decades, SiC particles, whiskers, and fibers have been continuously and extensively used to improve the key performance indicators of composite materials.
[0004] However, when graphene or silicon carbide is combined with aluminum alloy to prepare composite materials, due to the large specific surface area and thermodynamic and kinetic reasons, during the process of preparing composite materials with aluminum alloy using graphene or silicon carbide as reinforcement, the Mg element in the aluminum matrix will naturally segregate to the vicinity of graphene or silicon carbide, resulting in a decrease in the Mg element content in the aluminum matrix. This disrupts the original Mg-Si atomic ratio in the aluminum matrix, causing a change in the aging precipitation sequence of the composite material. The Mg2Si phase that should precipitate during the aging process becomes the B' phase, reducing the mechanical properties of the composite material. Summary of the Invention
[0005] To address the problem of Mg segregation in existing graphene or silicon carbide-based aluminum composite materials, this invention proposes a method for preparing graphene / aluminum composite materials by controlling Mg interfacial segregation using a dual-reinforcing phase, thereby achieving control over the diffusion direction of Mg, reducing interfacial segregation, and improving interfacial bonding strength.
[0006] The present invention utilizes a dual-reinforcement phase to regulate Mg element interfacial segregation in a graphene / aluminum composite material preparation method, which is carried out according to the following steps:
[0007] I. Weighing Materials
[0008] Weigh out 0.5%~2% graphene, 0.5%~2% process control agent, 3%~5% micron silicon carbide, 5%~10% nano silicon carbide and the balance 6061 aluminum metal powder as raw materials according to the mass fraction; weigh out aluminum alloy blocks, and the mass ratio of aluminum alloy blocks to 6061 aluminum metal powder is (5~10):1.
[0009] The average particle size of the micron-sized silicon carbide is 3~5μm;
[0010] The average particle size of the nano-silicon carbide is 150~500nm;
[0011] II. Preparation of Graphene-Silicon Carbide-Aluminum Precursors
[0012] First, the graphene and micron-sized silicon carbide weighed in step one are mixed and then subjected to low-energy ball milling. Then, the resulting mixed powder is mixed with nano-silicon carbide and 6061 aluminum metal powder and subjected to high-energy ball milling to obtain graphene-silicon carbide-aluminum composite powder.
[0013] The graphene-silicon carbide-aluminum composite powder was loaded into a steel mold and cold-pressed at room temperature. Then it was heated in a vacuum furnace to obtain a graphene-silicon carbide-aluminum preform.
[0014] Heating causes the process control agent to fully decompose and form a supporting structure at the interface, while simultaneously creating a tighter interface between the aluminum matrix and graphene and silicon carbide, thus improving the interfacial bonding strength. Graphene and micron-sized silicon carbide powder are then subjected to low-energy ball milling, which utilizes silicon carbide to initially reduce the number of graphene layers, thereby improving the reinforcement efficiency of graphene. Furthermore, low-speed ball milling effectively protects the graphene and reduces its breakage. Subsequently, the mixed powder is ball-milled with aluminum alloy powder at high energy to initially bond the reinforcing powder with the aluminum alloy powder.
[0015] The low-energy ball milling process is as follows: the ball-to-material ratio is (10~15):1, and the ball is milled at a speed of 30~60 rpm for 1~6 hours;
[0016] The high-energy ball milling process is as follows: the ball-to-material ratio is (5~10):1, and the ball milling is carried out at a speed of 200~250 rpm for 3~6 hours;
[0017] The vacuum heating furnace first heats to 300~350℃ and holds for 1~4 hours, then heats to 600~650℃ and holds for 2~6 hours, with a heating rate of 5~10℃ / min;
[0018] III. Aluminum Metal Infiltration and Preparation of Graphene-Silicon Carbide-Aluminum Composite Materials
[0019] The graphene-silicon carbide-aluminum preform obtained in step two and the aluminum alloy block weighed in step one are placed in a vacuum infiltration furnace. The preform is preheated, and the aluminum alloy block is melted to obtain an aluminum alloy melt. The aluminum alloy melt is poured into the preform mold, and pressure is applied to the melt for infiltration to obtain a graphene-silicon carbide-aluminum composite material ingot.
[0020] Under pressure, the aluminum alloy melt infiltrates into the preform and penetrates into the material along the gaps in the preform, making the composite material denser. Under the action of thermal pressure, the graphene and silicon carbide bond more tightly with the matrix, forming a denser interfacial bond.
[0021] The impregnation pressure is 100~150KN, and the pressure holding time is 15~25min;
[0022] IV. Hot Extrusion Processing
[0023] The graphene-silicon carbide-aluminum composite material ingot obtained in step three is loaded into a steel mold, heated and kept at a certain temperature, and then hot extruded to obtain an extruded rod.
[0024] The heating temperature of the hot extrusion is 400~500℃, the heating rate is 5~15℃ / min, the holding time is 1~3 hours, the extrusion speed is 15~20cm / min, and the diameter of the resulting extrusion bar is 10~15mm.
[0025] V. Homogenization of Components
[0026] The extrusion bar obtained in step four is then subjected to a component homogenization treatment to complete the process.
[0027] The homogenization process is carried out at a temperature of 520-560℃, with a holding time of 1-6 hours and a heating rate of 20-30℃ / min.
[0028] Principles and beneficial effects of this invention:
[0029] 1. This invention utilizes a mechanical ball milling process to first allow micron-sized silicon carbide to fully contact graphene. Under the action of the micron-sized silicon carbide, the graphene begins to reduce its layers, thus improving its reinforcing efficiency. Then, it is mixed with aluminum powder. This reduces interfacial damage between graphene and aluminum powder caused by direct ball milling, thereby optimizing interfacial bonding and load transfer, ultimately forming a graphene-silicon carbide-aluminum composite powder.
[0030] 2. In the preparation process of the graphene-silicon carbide-aluminum precursor, the present invention maintains a temperature of 300-350℃. The purpose of this is to allow the added process control agent to fully decompose at high temperature. The decomposed process control agent can naturally form a supporting skeleton at the interface. At the same time, graphene and silicon carbide can also tightly bond with the interface at high temperature, thereby improving the interfacial bonding strength of the composite material.
[0031] 3. In the pressure impregnation preparation process of this invention, since there are two reinforcing phases, graphene and silicon carbide, Mg elements begin to segregate towards the vicinity of the reinforcing phase during the impregnation process. However, since both graphene and silicon carbide have an attractive effect on Mg elements, Mg elements will not all segregate to the interface of one reinforcing phase, but will remain more in the matrix between graphene and silicon carbide. This reduces the amount of Mg element segregation at the interface, increases the Mg element content in the matrix, corrects the order of precipitated phases after solution aging of the composite material, and improves the comprehensive mechanical properties of the composite material.
[0032] 4. In the preparation process of this invention, hot extrusion is selected. Hot extrusion can improve the bonding strength between graphene and silicon carbide and aluminum matrix, promote grain refinement, improve the arrangement direction of graphene, and realize the directional arrangement of graphene. In addition, hot extrusion can increase the density of composite material, accelerate the diffusion of Mg element, realize the regulation of the diffusion direction of Mg element with dual reinforcement, and improve the interfacial bonding strength.
[0033] 5. This invention utilizes composition homogenization treatment to re-dissolve elements in the matrix into the aluminum lattice, forming solid solution strengthening. At the same time, under the action of the dual strengthening phase, the diffusion direction of Mg element is changed, reducing the segregation at the interface.
[0034] 6. The graphene-silicon carbide-aluminum composite material prepared by this invention has excellent comprehensive properties, with an elastic modulus exceeding 90 GPa, a tensile strength exceeding 630 MPa, and an elongation exceeding 11.6%;
[0035] 7. The overall process of this invention is clear and simple. The graphene is reduced in number of layers through mechanical ball milling, and the diffusion direction of Mg is changed through pressure impregnation and composition homogenization, which reduces the amount of Mg interfacial segregation. It does not involve chemical methods, has little environmental pollution, low cost, simple equipment, and is easy to apply in large-scale production.
[0036] 8. In the process of pressure impregnation, the use of aluminum alloy containing Si can correct the Mg-Si atomic ratio in the composite material, thereby assisting the reinforcing phase in controlling the interfacial segregation of Mg, correcting the precipitation sequence of the aging phase in the matrix, and improving the strength of the composite material. Attached Figure Description
[0037] Figure 1 Transmission EDS image of the composite material prepared in Example 1;
[0038] Figure 2 SEM and EDS images of the fracture surface of the composite material prepared in Example 1. Detailed Implementation
[0039] The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any reasonable combination of the specific embodiments.
[0040] Specific Implementation Method 1: This implementation method utilizes a dual-reinforcement phase to regulate Mg element interfacial segregation in graphene / aluminum composite materials, and is carried out according to the following steps:
[0041] I. Weighing Materials
[0042] Weigh out 0.5%~2% graphene, 0.5%~2% process control agent, 3%~5% micron silicon carbide, 5%~10% nano silicon carbide and the balance 6061 aluminum metal powder as raw materials according to the mass fraction; weigh out aluminum alloy blocks, and the mass ratio of aluminum alloy blocks to 6061 aluminum metal powder is (5~10):1.
[0043] The average particle size of the micron-sized silicon carbide is 3~5μm;
[0044] The average particle size of the nano-silicon carbide is 150~500nm;
[0045] II. Preparation of Graphene-Silicon Carbide-Aluminum Precursors
[0046] First, the graphene and micron-sized silicon carbide weighed in step one are mixed and then subjected to low-energy ball milling. Then, the resulting mixed powder is mixed with nano-silicon carbide and 6061 aluminum metal powder and subjected to high-energy ball milling to obtain graphene-silicon carbide-aluminum composite powder.
[0047] The graphene-silicon carbide-aluminum composite powder was loaded into a steel mold and cold-pressed at room temperature. Then it was heated in a vacuum furnace to obtain a graphene-silicon carbide-aluminum preform.
[0048] Heating causes the process control agent to fully decompose and form a supporting structure at the interface, while simultaneously creating a tighter interface between the aluminum matrix and graphene and silicon carbide, thus improving the interfacial bonding strength. Graphene and micron-sized silicon carbide powder are then subjected to low-energy ball milling, which utilizes silicon carbide to initially reduce the number of graphene layers, thereby improving the reinforcement efficiency of graphene. Furthermore, low-speed ball milling effectively protects the graphene and reduces its breakage. Subsequently, the mixed powder is ball-milled with aluminum alloy powder at high energy to initially bond the reinforcing powder with the aluminum alloy powder.
[0049] The low-energy ball milling process is as follows: the ball-to-material ratio is (10~15):1, and the ball is milled at a speed of 30~60 rpm for 1~6 hours;
[0050] The high-energy ball milling process is as follows: the ball-to-material ratio is (5~10):1, and the ball milling is carried out at a speed of 200~250 rpm for 3~6 hours;
[0051] The vacuum heating furnace first heats to 300~350℃ and holds for 1~4 hours, then heats to 600~650℃ and holds for 2~6 hours, with a heating rate of 5~10℃ / min;
[0052] III. Aluminum Metal Infiltration and Preparation of Graphene-Silicon Carbide-Aluminum Composite Materials
[0053] The graphene-silicon carbide-aluminum preform obtained in step two and the aluminum alloy block weighed in step one are placed in a vacuum infiltration furnace. The preform is preheated, and the aluminum alloy block is melted to obtain an aluminum alloy melt. The aluminum alloy melt is poured into the preform mold, and pressure is applied to the melt for infiltration to obtain a graphene-silicon carbide-aluminum composite material ingot.
[0054] Under pressure, the aluminum alloy melt infiltrates into the preform and penetrates into the material along the gaps in the preform, making the composite material denser. Under the action of thermal pressure, the graphene and silicon carbide bond more tightly with the matrix, forming a denser interfacial bond.
[0055] The impregnation pressure is 100~150KN, and the pressure holding time is 15~25min;
[0056] IV. Hot Extrusion Processing
[0057] The graphene-silicon carbide-aluminum composite material ingot obtained in step three is loaded into a steel mold, heated and kept at a certain temperature, and then hot extruded to obtain an extruded rod.
[0058] The heating temperature of the hot extrusion is 400~500℃, the heating rate is 5~15℃ / min, the holding time is 1~3 hours, the extrusion speed is 15~20cm / min, and the diameter of the resulting extrusion bar is 10~15mm.
[0059] V. Homogenization of Components
[0060] The extrusion bar obtained in step four is then subjected to a component homogenization treatment to complete the process.
[0061] The homogenization process is carried out at a temperature of 520-560℃, with a holding time of 1-6 hours and a heating rate of 20-30℃ / min.
[0062] 1. In this embodiment, a mechanical ball milling process is used to first allow micron-sized silicon carbide to come into full contact with graphene. Under the action of micron-sized silicon carbide, the graphene begins to reduce its layers, thus improving the reinforcing efficiency of the graphene. Then, it is mixed with aluminum powder. This reduces the interfacial damage between graphene and aluminum powder caused by direct ball milling, thereby optimizing interfacial bonding and load transfer, ultimately forming a graphene-silicon carbide-aluminum composite powder.
[0063] 2. In this embodiment, the graphene-silicon carbide-aluminum precursor is kept at 300-350℃. The purpose of this is to allow the added process control agent to fully decompose at high temperature. The decomposed process control agent can naturally form a supporting skeleton at the interface. At the same time, graphene and silicon carbide can also tightly bond with the interface at high temperature, thereby improving the interfacial bonding strength of the composite material.
[0064] 3. In this embodiment, during the pressure impregnation preparation process, since there are two reinforcing phases, graphene and silicon carbide, Mg elements begin to segregate towards the vicinity of the reinforcing phase during the impregnation process. However, since both graphene and silicon carbide have an attractive effect on Mg elements, Mg elements will not all segregate to the interface of one reinforcing phase, but will remain more in the matrix between graphene and silicon carbide. This reduces the amount of Mg element segregation at the interface, increases the Mg element content in the matrix, corrects the order of precipitated phases after solution aging of the composite material, and improves the comprehensive mechanical properties of the composite material.
[0065] 4. In this embodiment, a hot extrusion process is selected during the preparation process. The hot extrusion process can improve the bonding strength between graphene and silicon carbide and the aluminum matrix, promote grain refinement, improve the arrangement direction of graphene, and realize the directional arrangement of graphene. In addition, hot extrusion can increase the density of the composite material, accelerate the diffusion of Mg element, realize the regulation of the diffusion direction of Mg element with dual reinforcement, and improve the interfacial bonding strength.
[0066] 5. This embodiment utilizes composition homogenization treatment to re-dissolve elements in the matrix into the aluminum lattice, forming solid solution strengthening. At the same time, under the action of the dual strengthening phases, the diffusion direction of Mg elements is changed, reducing the segregation at the interface.
[0067] 6. The graphene-silicon carbide-aluminum composite material prepared in this embodiment has excellent comprehensive properties, with an elastic modulus exceeding 90 GPa, tensile strength exceeding 630 MPa, and elongation exceeding 11.6%;
[0068] 7. The overall process flow of this embodiment is clear and simple. The graphene is reduced in number of layers through mechanical ball milling, and the diffusion direction of Mg is changed through pressure impregnation and composition homogenization, which reduces the amount of Mg interfacial segregation. It does not involve chemical methods, has little environmental pollution, low cost, simple equipment, and is easy to apply in large-scale production.
[0069] 8. In this embodiment, the use of aluminum alloy containing Si during pressure impregnation can correct the Mg-Si atomic ratio in the composite material, thereby assisting the reinforcing phase in controlling the interfacial segregation of Mg, correcting the precipitation sequence of the aging phase in the matrix, and improving the strength of the composite material.
[0070] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the process control agent mentioned in step one is silicone oil.
[0071] Specific Implementation Method 3: This implementation method differs from Specific Implementation Method 1 or 2 in that the 6061 aluminum metal powder mentioned in step 1 is spherical powder with an average particle size of 5~15μm.
[0072] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: the aluminum alloy mentioned in step one is one or a combination of several of the following: Al-Si alloy, Al-Mg-Si alloy, Al-Si-Cu alloy, Al-Cu-Mg alloy, Al-Zn-Mg-Cu alloy, and Al-Si-Cu-Mg alloy; the mass fraction of Si in the Al-Si alloy is 2% to 25%; the mass fraction of Si in the Al-Mg-Si alloy is 0.5% to 25%, and the mass fraction of Mg is 0.5% to 50%; the mass fraction of Si in the Al-Si-Cu alloy is 0.5% to 25%, and the mass fraction of Cu is 0.5% to 53%. In Al-Cu-Mg alloys, the mass fraction of Cu is 0.5%~53%, and the mass fraction of Mg is 0.5%~38%; in Al-Zn-Mg-Cu alloys, the mass fraction of Zn is 0.5%~55%, the mass fraction of Mg is 0.5%~38%, and the mass fraction of Cu is 0.5%~53%; in Al-Si-Cu-Mg alloys, the mass fraction of Si is 0.5%~25%, the mass fraction of Cu is 0.5%~53%, and the mass fraction of Mg is 0.5%~38%.
[0073] Specific Implementation Method 5: This implementation method differs from one of the specific implementation methods 1 to 4 in that: the atmosphere inside the vacuum heating furnace in step 2 is a nitrogen atmosphere.
[0074] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the cold pressing pressure in step two is 50~70KN and the holding time is 15~30min.
[0075] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the preheating temperature of the preform in step three is 630~700°C, and the heat preservation time is 4~6 hours.
[0076] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that the melting temperature of the aluminum alloy block in step three is 830~880℃, and the heat is maintained for 3~8 hours.
[0077] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that: the heating temperature of the hot extrusion in step four is 450℃, the heating rate is 10℃ / min, the holding time is 2 hours, the extrusion speed is 15cm / min, and the diameter of the resulting extrusion bar is 12mm.
[0078] Specific Implementation Method 10: This implementation method differs from Specific Implementation Methods 1 to 9 in that the homogenization treatment temperature in step 5 is 550℃, the holding time is 3h, and the heating rate is 20℃ / min.
[0079] Example 1
[0080] This embodiment utilizes a dual-reinforcement phase to regulate Mg element interfacial segregation in a graphene / aluminum composite material preparation method, which is carried out according to the following steps:
[0081] I. Weighing Materials
[0082] Weigh out 1% graphene, 1% process control agent, 4% micron silicon carbide, 5% nano silicon carbide and the balance 6061 aluminum metal powder as raw materials by mass fraction; weigh out aluminum alloy blocks, with the mass ratio of aluminum alloy blocks to 6061 aluminum metal powder being 5:1.
[0083] The average particle size of the micron-sized silicon carbide is 5 μm;
[0084] The average particle size of the nano-silicon carbide is 400 nm.
[0085] The process control agent is silicone oil;
[0086] The 6061 aluminum metal powder is a spherical powder with an average particle size of 5 μm.
[0087] The aluminum alloy is 6061 alloy;
[0088] II. Preparation of Graphene-Silicon Carbide-Aluminum Precursors
[0089] First, the graphene and micron-sized silicon carbide weighed in step one are mixed and then ball-milled at low energy. Then, the resulting mixed powder is mixed with nano-sized silicon carbide and 6061 aluminum metal powder and ball-milled at high energy to obtain graphene-silicon carbide-aluminum composite powder. The graphene-silicon carbide-aluminum composite powder is loaded into a steel mold and cold-pressed at room temperature, then heated in a vacuum furnace to obtain a graphene-silicon carbide-aluminum preform. Heating allows the process control agent to fully decompose and form a supporting structure at the interface, while simultaneously forming a tighter interface between the aluminum matrix and graphene and silicon carbide, improving the interfacial bonding strength. Low-energy ball milling of the graphene and micron-sized silicon carbide powder utilizes silicon carbide to initially reduce the number of graphene layers, improving the reinforcement efficiency. Furthermore, low-speed ball milling effectively protects the graphene and reduces its breakage. Finally, the mixed powder is ball-milled with aluminum alloy powder at high energy to initially bond the reinforcing powder with the aluminum alloy powder.
[0090] The low-energy ball milling process is as follows: the ball-to-material ratio is 12:1, and the ball milling is carried out at a speed of 30 rpm for 6 hours;
[0091] The high-energy ball milling process is as follows: the ball-to-material ratio is 8:1, and the ball milling is carried out at 250 rpm for 4 hours.
[0092] The vacuum heating furnace first heats to 320°C and holds for 2 hours, then heats to 600°C and holds for 6 hours, with a heating rate of 10°C / min.
[0093] Step 2: The atmosphere inside the vacuum heating furnace is a nitrogen atmosphere;
[0094] The cold pressing pressure in step two is 50 kN, and the holding time is 30 min;
[0095] III. Aluminum Metal Infiltration and Preparation of Graphene-Silicon Carbide-Aluminum Composite Materials
[0096] The graphene-silicon carbide-aluminum preform obtained in step two and the aluminum alloy block weighed in step one are placed in a vacuum infiltration furnace. The preform is preheated, and the aluminum alloy block is melted to obtain an aluminum alloy melt. The aluminum alloy melt is poured into the preform mold, and pressure is applied to the melt for infiltration to obtain a graphene-silicon carbide-aluminum composite material ingot. Under pressure, the aluminum alloy melt infiltrates into the preform and penetrates into the material along the gaps in the preform, making the composite material more dense. Under the action of thermal pressure, the graphene and silicon carbide are more tightly bonded to the matrix, forming a denser interfacial bond.
[0097] The preheating temperature of the preform is 650°C, and the holding time is 5 hours.
[0098] The melting point of the aluminum alloy block is 880℃, and it is held at that temperature for 5 hours.
[0099] The impregnation pressure is 100KN, and the pressure holding time is 15min;
[0100] IV. Hot Extrusion Processing
[0101] The graphene-silicon carbide-aluminum composite material ingot obtained in step three is loaded into a steel mold, heated and kept at a certain temperature, and then hot extruded to obtain an extruded rod.
[0102] The heating temperature of the hot extrusion is 450℃, the heating rate is 10℃ / min, the holding time is 2 hours, the extrusion speed is 15cm / min, and the diameter of the resulting extrusion bar is 12mm.
[0103] V. Homogenization of Components
[0104] The extrusion bar obtained in step four is then subjected to a component homogenization treatment to complete the process.
[0105] The homogenization process is carried out at a temperature of 550°C for 3 hours and a heating rate of 20°C / min.
[0106] Figure 1 The transmission EDS image of the composite material prepared in Example 1 shows that Mg elements are segregated near the graphene. Figure 2 The SEM and EDS images of the fracture surface of the composite material prepared in Example 1 clearly show the location of SiC. The relatively uniform distribution of Mg in the composite material indicates that the dual reinforcement effectively improves Mg segregation. The graphene-silicon carbide-aluminum composite material prepared in this example has an in-plane yield strength of 453 MPa, a tensile strength of 630 MPa, and an elongation of 12.1%; a normal yield strength of 475 MPa, a tensile strength of 645 MPa, an elongation of 11.6%, and an elastic modulus of 95 GPa, demonstrating good overall performance.
[0107] Example 2
[0108] This embodiment utilizes a dual-reinforcement phase to regulate Mg element interfacial segregation in a graphene / aluminum composite material preparation method, which is carried out according to the following steps:
[0109] I. Weighing Materials
[0110] Weigh out 0.5% graphene, 0.5% process control agent, 5% micron silicon carbide, 5% nano silicon carbide and the balance 6061 aluminum metal powder as raw materials according to mass fraction; weigh out aluminum alloy block, the mass ratio of aluminum alloy block to 6061 aluminum metal powder is 8:1.
[0111] The average particle size of the micron-sized silicon carbide is 5 μm;
[0112] The average particle size of the nano-silicon carbide is 150 nm.
[0113] The process control agent is silicone oil;
[0114] The 6061 aluminum metal powder is a spherical powder with an average particle size of 10 μm.
[0115] The aluminum alloy is 4043 aluminum alloy;
[0116] II. Preparation of Graphene-Silicon Carbide-Aluminum Precursors
[0117] First, the graphene and micron-sized silicon carbide weighed in step one are mixed and then subjected to low-energy ball milling. Then, the resulting mixed powder is mixed with nano-silicon carbide and 6061 aluminum metal powder and subjected to high-energy ball milling to obtain graphene-silicon carbide-aluminum composite powder.
[0118] The graphene-silicon carbide-aluminum composite powder was loaded into a steel mold and cold-pressed at room temperature. Then it was heated in a vacuum furnace to obtain a graphene-silicon carbide-aluminum preform.
[0119] Heating causes the process control agent to fully decompose and form a supporting structure at the interface, while simultaneously creating a tighter interface between the aluminum matrix and graphene and silicon carbide, thus improving the interfacial bonding strength. Graphene and micron-sized silicon carbide powder are then subjected to low-energy ball milling, which utilizes silicon carbide to initially reduce the number of graphene layers, thereby improving the reinforcement efficiency of graphene. Furthermore, low-speed ball milling effectively protects the graphene and reduces its breakage. Subsequently, the mixed powder is ball-milled with aluminum alloy powder at high energy to initially bond the reinforcing powder with the aluminum alloy powder.
[0120] The low-energy ball milling process is as follows: the ball-to-material ratio is 8:1, and the ball milling is carried out at a speed of 50 rpm for 4 hours;
[0121] The high-energy ball milling process is as follows: the ball-to-material ratio is 8:1, and the ball milling is carried out at 200 rpm for 6 hours;
[0122] The vacuum heating furnace first heats to 300°C and holds for 4 hours, then heats to 650°C and holds for 2 hours, with a heating rate of 5°C / min.
[0123] Step 2: The atmosphere inside the vacuum heating furnace is a nitrogen atmosphere;
[0124] The cold pressing pressure in step two is 70 kN, and the holding time is 15 min;
[0125] III. Aluminum Metal Infiltration and Preparation of Graphene-Silicon Carbide-Aluminum Composite Materials
[0126] The graphene-silicon carbide-aluminum preform obtained in step two and the aluminum alloy block weighed in step one are placed in a vacuum infiltration furnace. The preform is preheated, and the aluminum alloy block is melted to obtain an aluminum alloy melt. The aluminum alloy melt is poured into the preform mold, and pressure is applied to the melt for infiltration to obtain a graphene-silicon carbide-aluminum composite material ingot.
[0127] Under pressure, the aluminum alloy melt infiltrates into the preform and penetrates into the material along the gaps in the preform, making the composite material denser. Under the action of thermal pressure, the graphene and silicon carbide bond more tightly with the matrix, forming a denser interfacial bond.
[0128] The preheating temperature of the preform is 630°C, and the holding time is 6 hours.
[0129] The melting point of the aluminum alloy block is 850℃, and it is held at that temperature for 8 hours.
[0130] The impregnation pressure is 150 kN, and the pressure holding time is 25 min;
[0131] IV. Hot Extrusion Processing
[0132] The graphene-silicon carbide-aluminum composite material ingot obtained in step three is loaded into a steel mold, heated and kept at a certain temperature, and then hot extruded to obtain an extruded rod.
[0133] The hot extrusion process involves a heating temperature of 500℃, a heating rate of 10℃ / min, a holding time of 1.5 hours, an extrusion speed of 20cm / min, and an extrusion bar diameter of 12mm.
[0134] V. Homogenization of Components
[0135] The extrusion bar obtained in step four is then subjected to a component homogenization treatment to complete the process.
[0136] The homogenization process is carried out at a temperature of 500°C for 3.5 hours and a heating rate of 30°C / min.
[0137] The graphene-silicon carbide-aluminum composite material prepared in this embodiment has an in-plane yield strength of 473 MPa, a tensile strength of 635 MPa, and an elongation of 12.3%; a normal yield strength of 500 MPa, a tensile strength of 660 MPa, an elongation of 11.7%, and an elastic modulus of 100 GPa. The composite material has good comprehensive performance.
Claims
1. A method for preparing graphene / aluminum composite materials by controlling Mg element interfacial segregation using dual-reinforcement phases, characterized in that: The preparation method of graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases is carried out according to the following steps: I. Weighing Materials Weigh out 0.5%~2% graphene, 0.5%~2% process control agent, 3%~5% micron silicon carbide, 5%~10% nano silicon carbide and the balance 6061 aluminum metal powder as raw materials according to the mass fraction; weigh out aluminum alloy blocks, and the mass ratio of aluminum alloy blocks to 6061 aluminum metal powder is (5~10):
1. The average particle size of the micron-sized silicon carbide is 3~5μm; The average particle size of the nano-silicon carbide is 150~500nm; II. Preparation of Graphene-Silicon Carbide-Aluminum Precursors First, the graphene and micron-sized silicon carbide weighed in step one are mixed and then subjected to low-energy ball milling. Then, the resulting mixed powder is mixed with nano-silicon carbide and 6061 aluminum metal powder and subjected to high-energy ball milling to obtain graphene-silicon carbide-aluminum composite powder. The graphene-silicon carbide-aluminum composite powder was loaded into a steel mold and cold-pressed at room temperature. Then it was heated in a vacuum furnace to obtain a graphene-silicon carbide-aluminum preform. The low-energy ball milling process is as follows: the ball-to-material ratio is (10~15):1, and the ball is milled at a speed of 30~60 rpm for 1~6 hours; The high-energy ball milling process is as follows: the ball-to-material ratio is (5~10):1, and the ball milling is carried out at a speed of 200~250 rpm for 3~6 hours; During the heating process of the vacuum heating furnace, the temperature is first raised to 300~350℃ and held for 1~4 hours, then raised to 600~650℃ and held for 2~6 hours, with a heating rate of 5~10℃ / min. III. Aluminum Metal Infiltration and Preparation of Graphene-Silicon Carbide-Aluminum Composite Materials The graphene-silicon carbide-aluminum preform obtained in step two and the aluminum alloy block weighed in step one are placed in a vacuum infiltration furnace. The preform is preheated, and the aluminum alloy block is melted to obtain aluminum alloy melt. The aluminum alloy melt is poured into a preform mold and pressure is applied to the melt for impregnation to obtain a graphene-silicon carbide-aluminum composite material ingot. The impregnation pressure is 100~150KN, and the pressure holding time is 15~25min; IV. Hot Extrusion Processing The graphene-silicon carbide-aluminum composite material ingot obtained in step three is loaded into a steel mold, heated and kept at a certain temperature, and then hot extruded to obtain an extruded rod. The heating temperature for hot extrusion is 400~500℃, the heating rate is 5~15℃ / min, the holding time is 1~3 hours, and the extrusion speed is 15~20cm / min; The diameter of the extrusion rod is 10~15mm; V. Homogenization of Components The extrusion bar obtained in step four is then subjected to a component homogenization treatment to complete the process. The homogenization process is carried out at a temperature of 520-560℃, with a holding time of 1-6 hours and a heating rate of 20-30℃ / min.
2. The method for preparing graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: The process control agent mentioned in step one is silicone oil.
3. The method for preparing graphene / aluminum composite materials by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: The 6061 aluminum metal powder mentioned in step one is a spherical powder with an average particle size of 5~15μm.
4. The method for preparing graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: The aluminum alloy mentioned in step one is one or a combination of several of the following: Al-Si alloy, Al-Mg-Si alloy, Al-Si-Cu alloy, Al-Cu-Mg alloy, Al-Zn-Mg-Cu alloy, and Al-Si-Cu-Mg alloy. The mass fraction of Si in Al-Si alloys is 2% to 25%; In Al-Mg-Si alloys, the mass fraction of Si is 0.5%~25%, and the mass fraction of Mg is 0.5%~50%. In Al-Si-Cu alloys, the mass fraction of Si is 0.5%~25%, and the mass fraction of Cu is 0.5%~53%. In Al-Cu-Mg alloys, the mass fraction of Cu is 0.5%~53%, and the mass fraction of Mg is 0.5%~38%. In Al-Zn-Mg-Cu alloys, the mass fraction of Zn is 0.5%~55%, the mass fraction of Mg is 0.5%~38%, and the mass fraction of Cu is 0.5%~53%. In Al-Si-Cu-Mg alloys, the mass fraction of Si is 0.5%~25%, the mass fraction of Cu is 0.5%~53%, and the mass fraction of Mg is 0.5%~38%.
5. The method for preparing graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: Step 2: The atmosphere inside the vacuum heating furnace is a nitrogen atmosphere.
6. The method for preparing graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: The cold pressing pressure in step two is 50~70KN, and the holding time is 15~30min.
7. The method for preparing graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: The preheating temperature of the preform in step three is 630~700°C, and the heat preservation time is 4~6 hours.
8. The method for preparing graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: The melting temperature of the aluminum alloy block in step three is 830~880℃, and the holding time is 3~8h.
9. The method for preparing graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: The heating temperature for hot extrusion in step four is 450℃, the heating rate is 10℃ / min, the holding time is 2 hours, the extrusion speed is 15cm / min, and the diameter of the resulting extrusion bar is 12mm.
10. The method for preparing graphene / aluminum composite material by controlling Mg element interfacial segregation using dual-reinforcement phases according to claim 1, characterized in that: The homogenization process described in step five is carried out at a temperature of 550℃, a holding time of 3 hours, and a heating rate of 20℃ / min.
Citation Information
Cited By
Composite material and preparation method thereof, chassis and semiconductor equipment
CN122147122A
